Sesame (Sesamum indicum L.) seeds and di ammonium phosphate (dap) potential for controlling Striga seed germination, sorghum growth and grain yield - Abdou Ousseini Ardaly; Aissata Ibrahim Mamadou; Saviour Yaw Eleblu John; Ofori Kwadwo (Journal of Precision Agriculture, 2024)
Sorghum is important staple food for feeding humans and animals in sub-Saharan African country. Nowadays, with the advent of climate change couple to the population growth, the crop is faced to new challenges wish are gradually affecting the productivity. In Niger, a dry land country where farmers are growing sorghum at a small scale for family subsistence, the crop is confronted to biotic and abioticonstraints including nutrient deficiency in the soil. Among those constraint, Striga is the one that causes huge damage to sorghum cultivation through yield reduction. In addition, nutrient depletion in the soil are causing weed progresses in farmer’s field at a large scale. In fact, to overcome Striga problem several control methods have been successfully tested, but some of them are efficient but not accessible to farmers. It is important to control the weed by using effective and accessible way for smallholder farme in Niger. The main objective of this study was to assess the effectiveness of different doses of sesame (0, 0.5 and 1.5 g) and DAP (0, 2 and 5 g) on Striga impact and sorghum grain yield. Two (2) grammes micro dosing utilization of DAP shows good result in Striga plant emergency and distribution along sorghum field. Concerning the three doses of sesame seed involve in this experiment, the micro dosing two (1.5 g) positively affect Striga effect. The combination sesame seed and DAP can significantly reduce Striga impact on sorghum cultivation and increased sorghum grain yield.
Keywords: Striga